Pengaruh Etika Profesi Akuntan Publik Dan Kompetensi Auditor Terhadap Kualitas Audit: Studi Kasus Pada KAP Suherman, SE., Ak., CA. CPA Di Bandar Lampung - Yesi Anjas Wahyuni, Eka; Rizal, Syamsu (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
As public accountants and auditors, they need to understand and follow the professional code of ethics related to professional responsibility, competence, and due care, confidentiality, professional attitude, and technical requirements in implementing their profession. The higher the quality standard and code of ethics, the higher the audit quality (Yusri, 2020). This finding was carried out at the Public Accounting Firm (KAP). Since KAP was launched in 2018, the challenges in research related to the implementation of quality control standards and ethics of the public accounting profession are relatively new. The purpose of this finding is to prove whether the professional ethics of public accountants and auditor competence have combined effection audit quality, as well as which variables are the most important in influencing audit quality. The total participants in this finding were 30 (thirty), with 1 (one) public accountant and 29 (twenty-nine) auditors working at KAP Suherman., SE., AK., CA. BPK in Bandar Lampung. Validity and reliability tests were used in the data instrument test, while descriptive and quantitative data analysis were used when analyzing the data. Based on these findings, the professional ethic of public accountants and the competence of auditors have a significant influence on audit quality.